"A content analysis of news media coverage of drowning events in Western Australia over two summers, 2014‐2016". (19th June 2019) - Leavy, Justine E.; Jancey, Jonine; Hall, Carmen; Nimmo, Lauren; Crawford, Gemma
Abstract: Issue addressed: Drowning is a leading cause of death globally. Opportunities to promote drowning prevention in news media may be overlooked for attention‐grabbing headlines, imagery and narrative. This study examines news media coverage of fatal drowning events in Western Australia (WA). Methods: Coronial fatal drowning data in WA were extracted for two summer time periods (2014‐2016) by date, age, gender, location and description. Corresponding print and online news articles were captured using: (i) Media Alert; (ii) Google News; (iii) Factiva. A content and frame analysis protocol was developed. A qualitative approach was taken to analyse the news angle. A subgroup analysis was undertaken for drowning focused articles. Results: The final sample (n = 50) news articles matched 17 individual drowning events (T1, n = 9; T2, n = 8). Drowning stories rarely appeared on page 1 (n = 2), but were located in the first 2‐10 pages (n = 20) (66.6%). In the subanalysis, one‐fifth (22%) of the articles employed a news angle relating to community spirit and celebration of life. There were 32 mentions of "who was responsible for the drowning event." Environmental factors were most cited for "what was responsible" (20.4%). Experts were cited in 66.7% of articles and drowning prevention strategies were mentioned in nine of the 50 articles. Conclusion: Drowning was considered newsworthy; however, not the front page news. Reporting infrequently prioritised drowning prevention or discussed prevention strategies. So what?: Working closely with news outlets to embed drowning prevention messages in news stories during high‐risk periods such as summer is an imperative.